Social-Emotional Value and Coffee Milk eWOM: Mediation of Satisfaction and Engagement - Raden Muhammad Fikri Akbar; Anny Nurbasari (Jurnal Informatika Ekonomi Bisnis, 2026)
This study investigates the influence of perceived social-emotional value on electronic word-of-mouth among Indonesian coffee milk consumers, specifically examining the mediating roles of customer satisfaction and customer engagement. Method: A quantitative study using a causal-explanatory design was conducted. Data were collected via an online survey from 200 purposively sampled respondents who are active on social media. The data were analyzed using Partial Least Squares Structural Equation Modelling with SmartPLS 4.0. Findings: The results demonstrate that Perceived Social-Emotional Value significantly influences both Customer Satisfaction (β = 0.878) and Customer Engagement (β = 0.897). Crucially, while both mediators positively drive eWOM, Customer Engagement exerts a much stronger influence (β = 0.564) compared to Customer Satisfaction (β = 0.293). The analysis confirms that social-emotional value indirectly fosters eWOM through both pathways, with engagement serving as the dominant behavioral driver. Implications: Theoretically, this research specifies the role of non-functional value in driving eWOM. Practically, findings guide managers to focus on creating shared social and emotional experiences to foster positive digital advocacy.